Interaction of microorganisms with the environment - Voitovich, A. V.; Yeryomina, A. K.; Kamyshny, A. M.; Sokolovska, I. A.; Войтович, Олександр Васильович; Єрьоміна, Алла Кузьмівна; Камишний, Олександр Михайлович; Соколовська, Ірина Анатоліївна (Zaporozhye state medical university, 2015)
Microecology a new scientific and practical fields of biology and medicine, located at the intersection of microbiology, ecology, epidemiology and hygiene, which is important for the further study of clinical microbiology. The data symbiotic relationships between organisms themselves and with the human body. Paid much attention to positive and negative effects on human health microbiota different environmental habitats and habitats of various human body. The basic methods of sanitary microbiology and virology.
Взаємодія мікроорганізмів з навколишнім середовищем
Keywords: мікробіологія; микробиология; microbiology